Public Relations Crisis Management of The Environment and Forestry Office Of DIY in Handling The Closure of The Integrated Waste Disposal Site (TPST) by The Community in Piyungan - yeni rosilawati; DISTIAN AJI (Jurnal Ilmu Komunikasi, 2021)
The Environment and Forestry Office (DLHK) of the Special Region of Yogyakarta (DIY) is a government agency that manages the Integrated Waste Disposal Site (TPST) located in Piyungan. In the TPST, there is dissatisfaction from the local community regarding the management system. The peak is the closure of Piyungan TPST by the local community as a form of their dissatisfaction. This problem impacts the survival of the surrounding community and the emergence of demands for the DLHK. This study aims to determine the crisis management steps selected by the DLHK of DIY in dealing with crisis management issues and restoring the image of the institution. This study utilized descriptive qualitative as the research method. The data were collected through interviews with the public relations (PR) officer of the Piyungan TPST of the DLHK, a member of the Regional People’s Representative Council (DPRD) of DIY, and community members. Moreover, the data were supported by documentation data in the form of mass media clippings. The qualitative data analysis technique was applied to collect, present, and conclude data. This research discovered that the PR of the DLHK employed prevention, preparation, and mitigation strategies through changing policies and communication patterns by committing direct dialogue, compromise, and negotiation with the local community to overcome the crisis. The dialogue was also carried out on a routine basis; thus, the Piyungan TPST of the DLHK could determine the shortcomings, complaints, and opinions of the surrounding community.